The slippery slope: Can motivation and perfectionism lead to burnout in coaches? - Vealey, R. S.; Martin, E.; Coppola, A.; Ward, R. M.; Chamberlin, J. (International Sport Coaching Journal, 2020)
The purpose of the study was to investigate the relationships between perfectionism, motivation, burnout, and coaching satisfaction in high school and collegiate coaches (n=311). Coaches completed the modified Maslach Burnout Inventory, the Behavioral Regulation in Sport Questionnaire, the Multidimensional Perfectionism Scale, and an investigator-designed survey to assess satisfaction. As predicted, perfectionism was related to both motivation and burnout. In particular, socially-prescribed perfectionism emerged as the most significant type of perfectionism, showing positive relationships with controlled forms of motivation and burnout and negative relationships with autonomous forms of motivation and feelings of personal accomplishment. Self-oriented perfectionism was related to motivation, but not directly related to burnout, and other-oriented perfectionism was not significantly related to motivation or burnout. Autonomous motivation was strongly associated with coaches` satisfaction. The influence of socially-prescribed perfectionism on coaches is discussed in relation to the high expectations placed on coaches by programs and communities, perhaps contributing to feelings of low autonomy and external regulation. Controlling forms of social expectations and external regulation may act as a "slippery slope" in which the initial motivation of coaches may move toward burnout.